Relaxation oscillations of electrically coupled neuron-like systems with delay - S. D. Glyzin (Моделирование и анализ информационных систем, 2010)
The system of diffusion couplexl nonlinear differential-difference equations with delay modelling the elexctrical interacction of pulse neurons is studiexl. Given the spexxl of electrical processes in the system is high, the limit system, responsible for relaxation ccydes, is construcctexL Along with a synchronous cycle the system permits stable asynchronous ccydes, which asymptotics are presentexL